The effect of Biomass Shapes on combustion characteristic in updraft chamber - Suksuwan, Wasu; Mohideen Batcha, Mohd Faizal; Palamanit, Arkom; Wae-hayee, Makatar (Universiti Tun Hussein Onn Malaysia (UTHM), 2021)
The objective of this work was to study the effect of biomass shapes on combustion characteristic in an updraft chamber. 6 types of biomasses: rubber wood chips, coconut shell, oil palm empty fruit bunch, corn straw, rubber wood sawdust, and mixed palm cake that are agricultural wastes in Thailand were categorized by 3 shapes namely: chip shape, fiber shape, and powder shape. They were burnt using a combustion chamber, which was a simple type of direct combustion. The diameter of combustion chamber was 20 cm and the total height of the combustion chamber was 160 cm. Biomass sample, which moisture content was lower than 20%, was fixed at 1 kg per experiment for burning. The air velocity was varied at 0.50, 0.75 and 1.00 m/s which corresponds to an equivalence ratio between 1 up to 3.5. The temperature at different positions along combustion chamber height and the properties of product gas (carbon monoxide) were measured. The experimental results show that the biomass shape influences the combustion process. The fiber shape has low combustion temperature and higher carbon monoxide, which is indicated improper combustion. The chip shape was well burnt with higher air velocity and the product gas has the lowest amount of carbon monoxide. In addition, it had lower temperature than powder shapes. As for the powder shapes, it shows suitability for combustion with an updraft combustion chamber because it has the highest temperature compared with other types of biomass. However, it has some limitation for some powder biomass types as sawdust. When the air velocity was high, there was carryover of biomass particles without burning.